2018
DOI: 10.1017/s0022215118002220
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Coblation compared with cold steel tonsillectomies in the UK

Abstract: ObjectiveThis study aimed to estimate the cost-effectiveness of Coblation compared with cold steel tonsillectomy in adult and paediatric patients in the UK.MethodDecision analysis was undertaken by combining published clinical outcomes with resource utilisation estimates derived from a panel of clinicians.ResultsUsing a cold steel procedure instead of Coblation is expected to generate an incremental cost of more than £2000 for each additional avoided haemorrhage, and the probability of cold steel being cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A study conducted in the United Kingdom highlighted that coblation is a cost-effective intervention for tonsillectomy when compared with cold steel procedures for both adult and pediatric patients, with a probability of at least .7 at being costeffective. 24 In another study conducted in the United States, coblation was reported to have significantly lower costs compared to electrocautery surgery; however, the total cost of coblation was slightly higher when central supply was taken into account. 25 Based upon the results from the best available evidence comparing coblation tonsillectomy to bipolar diathermy in adult patients, there is no significant difference in the outcomes between the 2 techniques apart from more rapid healing of the tonsillar fossae in the coblation technique.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted in the United Kingdom highlighted that coblation is a cost-effective intervention for tonsillectomy when compared with cold steel procedures for both adult and pediatric patients, with a probability of at least .7 at being costeffective. 24 In another study conducted in the United States, coblation was reported to have significantly lower costs compared to electrocautery surgery; however, the total cost of coblation was slightly higher when central supply was taken into account. 25 Based upon the results from the best available evidence comparing coblation tonsillectomy to bipolar diathermy in adult patients, there is no significant difference in the outcomes between the 2 techniques apart from more rapid healing of the tonsillar fossae in the coblation technique.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted in the United Kingdom highlighted that coblation is a cost-effective intervention for tonsillectomy when compared with cold steel procedures for both adult and paediatric patients, with a probability of at least 0.7 at being cost-effective 26 . In another study conducted in the United States, coblation was reported to have significantly lower costs compared to electrocautery surgery, however, the total cost of coblation was slightly higher when central supply was taken into account 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, when central supply is put into consideration the total cost of coblation is slightly higher 27 ($2,646 versus $2,591; P = 0.0011) with a difference of $55.94. However, because coblation is less likely to result in severe hemorrhage, it was found that using coblation tonsillectomy could save the National Health Service in the United Kingdom an incremental cost of £2000 for every avoided hemorrhage as opposed to using cold dissection with bipolar diathermy for haemostasis 28 . In a retrospective audit of 1,336 patients who had undergone coblation, it was reported that this technique had an increased requirement for operative intervention to manage secondary haemorrhage 29 .…”
Section: Discussionmentioning
confidence: 99%